2010
DOI: 10.4103/0970-9290.70800
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial activity of various concentrations of Tulsi (Ocimum sanctum) extract against Streptococcus mutans: An in vitro study

Abstract: Tulsi extract demonstrated an antimicrobial property against Streptococcus mutans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 1 publication
2
78
0
1
Order By: Relevance
“…Ocimum sanctum is found to inhibit S. aureus at a concentration of 20% and E. coli at a concentration of 10% and C. aurantifolia inhibited S. aureus and E. coli at 15% and 10% concentration respectively, while the methanolic extracts of Cassia fistula was only able to inhibit E. coli and S. aureus at 60% concentration. Agarwal et al [39] found that Ocimum sanctum extracts can inhibit Streptococcus species at even 4% concentration. Methanolic extract of Polyalthia longifolia against E. coli and S. aureus was active at concentration of 40% and 60% respectively.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Ocimum sanctum is found to inhibit S. aureus at a concentration of 20% and E. coli at a concentration of 10% and C. aurantifolia inhibited S. aureus and E. coli at 15% and 10% concentration respectively, while the methanolic extracts of Cassia fistula was only able to inhibit E. coli and S. aureus at 60% concentration. Agarwal et al [39] found that Ocimum sanctum extracts can inhibit Streptococcus species at even 4% concentration. Methanolic extract of Polyalthia longifolia against E. coli and S. aureus was active at concentration of 40% and 60% respectively.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Tulsi, scientifically known as Ocimum sanctum (family Lamiaceae), is a time-tested premier medicinal herb of Indian origin, worshipped by Hindus and used in Ayurvedic medicine. It is bestowed with enormous antimicrobial substances and is used to treat a variety of illnesses ranging from diabetes mellitus, arthritis, bronchitis, skin diseases, etc., [11].…”
Section: Mm)mentioning
confidence: 99%
“…It is also reported that 4% tulsi extract has maximum antimicrobial activity against S.Mutans which indicates its anticaries activity. Because of its essential oil and its main components (eugenol and linalool) tulsi also has antifungal activity against C.albicans [6,7] Morindacitrifolia(Noni) It is also called as Indian Mulberry. Its juice has therapeutic effects including antibacterial, antiinflammatory, antiviral, antitumor, antihelmenthic, analgesic, hypotensive, anti-inflammatory and immune enhancing effects.…”
Section: Ocimum Sanctum (Tulsi)mentioning
confidence: 99%